2007
DOI: 10.1016/j.nuclphysa.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Cold uniform matter and neutron stars in the quark–meson-coupling model

Abstract: A new density dependent effective baryon-baryon interaction has been recently derived from the quark-meson-coupling (QMC) model, offering impressive results in application to finite nuclei and dense baryon matter. This self-consistent, relativistic quark-level approach is used to construct the Equation of State (EoS) and to calculate key properties of high density matter and cold, slowly rotating neutron stars. The results include predictions for the maximum mass of neutron star models, together with the corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
172
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(178 citation statements)
references
References 59 publications
6
172
0
Order By: Relevance
“…This behavior is different from the previous works that adopt attractive potentials [1,2,3,4,5], and pointed out in Refs. [2,3,4,38]. When we allow the appearance of pions, condensed pions (π − ) appear prior to hyperons.…”
Section: Neutron Star Mattermentioning
confidence: 99%
“…This behavior is different from the previous works that adopt attractive potentials [1,2,3,4,5], and pointed out in Refs. [2,3,4,38]. When we allow the appearance of pions, condensed pions (π − ) appear prior to hyperons.…”
Section: Neutron Star Mattermentioning
confidence: 99%
“…5, where we note that the species fraction is enhanced and the species fractions are suppressed with increasing density. From the investigations by Rikovska-Stone et al [16], we expect that the would disappear entirely if we were to include Fock terms.…”
Section: Resultsmentioning
confidence: 94%
“…For this purpose, we consider hadronic matter modeled by the quark-meson coupling (QMC) model [14,15], which was recently improved through the self-consistent inclusion of color hyperfine interactions [16]. While this improvement had no significant effect on the binding of nucleons, it led to impressive results for finite hypernuclei [17].…”
Section: Introductionmentioning
confidence: 99%
“…[16], where Σ hypernuclei could be bound by an amount similar to Λ hypernuclei. Recently, the QMC model has been extended to include the quark-quark hyperfine interactions due to gluon and pion exchanges [52][53][54][55]. It was found that the hyperfine interaction due to the gluon exchange plays an important role in the in-medium baryon spectra, while the pion-cloud effect is relatively small [55].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the hyperfine interaction due to the gluon exchange plays an important role in the in-medium baryon spectra, while the pion-cloud effect is relatively small [55]. Furthermore, the hyperfine interaction can make the equation of state hard and thus enhance the mass of a neutron star [52,56]. The medium effect on the hyperfine interaction increases the splitting between the Λ and Σ masses as the density rises, and Σ hypernuclei are found to be unbound in Ref.…”
Section: Introductionmentioning
confidence: 99%